2017
DOI: 10.1002/jls.21498
|View full text |Cite
|
Sign up to set email alerts
|

Film Narratives and Lessons in Leadership: Insights From the Film & Leadership Case Study (FLiCS) Club

Abstract: Feature films are used as case studies to highlight key leadership concepts in an undergraduate course in a business school. How each film constructs leadership in a particular way is problematized by noting the prevailing leadership discourses to which their narratives contribute, and the strengths and limitations of each. This analysis enables students to consider how a film's portrayal of leadership reflects and influences the various practices of leadership, for good and bad. Films also allude to the emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Given that these three emotions are considered important indicators in marketing research related to emotional contagion, the perceived charismatic leadership towards evil characters in the film can be inferred to have a significant impact on the emotional contagion of the audience. This finding is consistent with previous studies in film narrative studies (Long 2017;Kuri and Kaufman 2020). In contrast to the abstract nature of film and TV drama theories and their absence of empirical validation, this study empirically validated character arc theory and charismatic leadership theory of film and TV drama narratives by using empirical methods as well as linking them with tourism marketing theories.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Given that these three emotions are considered important indicators in marketing research related to emotional contagion, the perceived charismatic leadership towards evil characters in the film can be inferred to have a significant impact on the emotional contagion of the audience. This finding is consistent with previous studies in film narrative studies (Long 2017;Kuri and Kaufman 2020). In contrast to the abstract nature of film and TV drama theories and their absence of empirical validation, this study empirically validated character arc theory and charismatic leadership theory of film and TV drama narratives by using empirical methods as well as linking them with tourism marketing theories.…”
Section: Discussionsupporting
confidence: 88%
“…Through these dramas and films as an attractive medium, many studies have also found that individuals' perceptions of charismatic leadership from fictional characters can affect personal behaviour in reality. A character's charismatic leadership could be the impact of media portrayals on viewers' expectations, the reinforcement of social and cultural norms and the potential for leadership lessons to be derived from fictional narratives (Long 2017;Kuri and Kaufman 2020). The public's fascination with the images and behaviours of highly appealing film characters can be extended to the physical environments in which these characters appear (Allen, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They recommended that movies be used in leadership classrooms as an effective way to teach leadership lessons. Wimmer, Meyers, Porter, and Shaw (2012) and Long (2017) also found that movies can be used in different classroom situations for teaching purposes. The following steps may be adopted by teachers or instructors to use the movies in the classroom:…”
Section: U S E O F F I L M a S A T E Ac H I N G To O L: T H E T E Ac mentioning
confidence: 99%
“…Rajendran and Andrew (), for instance, have demonstrated the value of relying on films like Elizabeth (Shekhar Kapur, 1998), and Gandhi (Richard Attenborough, 1982) to enable students to critically assess the behavior of leaders. Long () has drawn an extensive list of useful dramas and documentaries from what he calls the “Film & Leadership Case Study Club” (or “FLiCS” Film Club), which range from Citizen Kane (Orson Welles, 1941) to Harry Potter and the Deathly Hallow Part II (David Yates, 2011). However, Long and other scholars have generally ignored the horror film as an effective genre to study leadership.…”
Section: Introduction: Leadership In the Face Of A Monstrous Threatmentioning
confidence: 99%